Inquiry-Based Science Education: Perspectives from Namibian Teachers - Shivolo, Tomas; Omari Mokiwa, Hamza (Universitas Terbuka, 2024)
In the evolving landscape of secondary school science education in Namibia, there is a growing shift from traditional rote-learning methodologies toward inquiry-based instruction and practical work to foster deeper learner engagement and critical thinking skills. This study, utilizing a sequential explanatory mixed methods approach, investigates the perceptions and practices of Namibian secondary school teachers regarding the implementation of inquiry-based science education. Despite the national curriculum's strong endorsement of learner-centered approaches, findings indicate a discrepancy between policy aspirations and classroom realities. Many teachers continue to rely on traditional methods due to persistent challenges such as inadequate resources, insufficient professional development, and entrenched instructional habits. However, those teachers who have adopted inquiry-based strategies report enhanced student engagement and a more profound understanding of scientific concepts among learners. This paper underscores the necessity for targeted professional development and resource allocation to bridge the gap between educational policy and practice, ultimately aiming to enrich science education through effective inquiry-based learning environments.